Affordances in crop diversification: Three cases from the Philippines - Leon, Teresa Joi P. de; IV, Jaime A. Manalo (Asian Journal of Agriculture and Rural Development, 2024)
This paper investigated the viability of crop diversification as an alternative production system for Filipino rice farmers in light of the Rice Tariffication Law. Qualitative research methods were employed, including focus group discussions, key informant interviews, in-depth interviews, and wind-screen survey. The transcript analysis employed both inductive and deductive approaches, supplemented by auditability measures such as coding guides and informal member-checking. Using the Affordances Theory with additional insights from the Capabilities Theory and Intuitive Decision-Making Theory, the findings show that rice farmers in Nueva Ecija, Ilocos Norte, and Tarlac shared one cognitive process and one set of variables in deciding on diversifying crops. This is despite the provincial differences in farming contexts. Affordances and anti-affordances in crop diversification are dependent on farmers’ visual and tracking experiences, which guide them in their evaluation of crop diversification as a pro-welfare farming practice. They evaluate the suitability of crop diversification for their sociocultural, economic, and farming contexts, but then shift to intuitive decision-making for their ultimate decision. Risks that are mostly external to farmer control, such as sufficiency of irrigation, financial capital, weather, and climate, make them conclude in a posture of luck after a detailed evaluation process on the practice of crop diversification. This study provides insights into using crop diversification as an alternative production system for rice farmers.